2019 IEEE Intelligent Transportation Systems Conference (ITSC) 2019
DOI: 10.1109/itsc.2019.8917390
|View full text |Cite
|
Sign up to set email alerts
|

Improving Map Re-localization with Deep ‘Movable’ Objects Segmentation on 3D LiDAR Point Clouds

Abstract: Localization and Mapping is an essential component to enable Autonomous Vehicles navigation, and requires an accuracy exceeding that of commercial GPS-based systems. Current odometry and mapping algorithms are able to provide this accurate information. However, the lack of robustness of these algorithms against dynamic obstacles and environmental changes, even for short time periods, forces the generation of new maps on every session without taking advantage of previously obtained ones. In this paper we propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…One challenge for map generation is the presence of dynamic objects and temporary obstacles, which require continuous updating of the map. [100] used a deep learning architecture to construct a durable map from 3D LiDAR data by filtering removable objects based on the convolutional dual-view architecture, which helps the ego vehicle for LiDAR-based re-localization and trajectory estimation. Another example of object detection and removable object substitution by the CNN is shown in [101].…”
Section: A Neural Networkmentioning
confidence: 99%
“…One challenge for map generation is the presence of dynamic objects and temporary obstacles, which require continuous updating of the map. [100] used a deep learning architecture to construct a durable map from 3D LiDAR data by filtering removable objects based on the convolutional dual-view architecture, which helps the ego vehicle for LiDAR-based re-localization and trajectory estimation. Another example of object detection and removable object substitution by the CNN is shown in [101].…”
Section: A Neural Networkmentioning
confidence: 99%
“…In an attempt to improve the accuracy of localization, in [167] Vaquero et al suggested improving the quality of the prebuilt map first. They proposed segmentation of the dynamic moving objects in the map, such as other vehicles and pedestrians, in order to obtain a map that is valid for use for a longer period.…”
Section: Map-matching-based Localizationmentioning
confidence: 99%
“…We use Cartographer (Hess et al 2016) Baselines: We evaluate our model with two baselines: (1) A unprocessed dynamic frame (Pure-Dynamic) and ( 2) With an efficient LiDAR pre-processing step for handling SLAM in dynamic environment which removes the dynamic points from the LiDAR scan (Detect & Delete) (Ruchti and Burgard 2018;Vaquero et al 2019).…”
Section: Application Of Lidar Scan Reconstruction For Slam In Dynamic...mentioning
confidence: 99%